2003
DOI: 10.1128/aem.69.4.2386-2388.2003
|View full text |Cite
|
Sign up to set email alerts
|

The Surface-Associated and Secreted MopE Protein of Methylococcus capsulatus (Bath) Responds to Changes in the Concentration of Copper in the Growth Medium

Abstract: Expression of surface-associated and secreted protein MopE of the methanotrophic bacterium Methylococcus capsulatus (Bath) in response to the concentration of copper ions in the growth medium was investigated. The level of protein associated with the cells and secreted to the medium changed when the copper concentration in the medium varied and was highest in cells exposed to copper stress

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
35
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 21 publications
2
35
0
Order By: Relevance
“…It is well-known that methanotrophic metabolism is strongly affected by copper and that methanotrophs utilize multiple mechanisms for copper uptake (1,(17)(18)(19)(20)(21)(22)(23)(24). Further, it has been shown that in M. trichosporium OB3b, methanobactin plays a significant role in controlling gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that methanotrophic metabolism is strongly affected by copper and that methanotrophs utilize multiple mechanisms for copper uptake (1,(17)(18)(19)(20)(21)(22)(23)(24). Further, it has been shown that in M. trichosporium OB3b, methanobactin plays a significant role in controlling gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple mechanisms by which aerobic proteobacterial methanotrophs collect copper, including a membranebound copper binding protein, MopE (ϳ66 kDa), as well as a truncated form of MopE (ϳ46 kDa), termed MopE*, that is secreted into the growth medium (17)(18)(19). This mechanism to date, however, has been characterized only from Methylococcus capsulatus Bath.…”
mentioning
confidence: 99%
“…That is, it has been shown that in M. album BG8, there exists an outer membrane protein, CorA, that is copper repressible and may serve to bind copper (44). Further, it has been found that M. capsulatus Bath synthesizes a similar outer membrane protein, MopE, as well as a secreted truncated form, MopE*, both of which bind Cu(II) (45)(46)(47). A gene encoding a protein similar to CorA and MopE, mbnP, is adjacent to the methanobactin gene cluster in M. trichosporium OB3b (36), and it may be that this serves as an alternative copper uptake mechanism in M. trichosporium OB3b.…”
Section: Discussionmentioning
confidence: 99%
“…The first step in methane metabolism, the oxidation of methane to methanol, is catalyzed by methane monooxygenase (MMO) metalloenzymes by either a copper-dependent membranebound particulate MMO (pMMO) (9) or an iron-dependent, soluble MMO (sMMO) (18). Therefore, metals are necessary for the growth of methanotrophic bacteria (12,13). Despite the importance of metals in methanotroph physiology, uptake of metal ions by methanotrophic bacteria is not well understood.…”
mentioning
confidence: 99%